Capsaicin treatment reduces nasal hyperreactivity and transient receptor potential cation channel subfamily V, receptor 1 (TRPV1) overexpression in patients with idiopathic rhinitis - Van Gerven, Laura; Alpizar, Yeranddy A.; Wouters, Mira M.; Hox, Valérie; Hauben, Esther; Jorissen, Mark; Boeckxstaens, Guy; Talavera, Karel; Hellings, Peter W. (Journal of allergy and clinical immunology, 2014)
Idiopathic rhinitis (IR) is a prevalent condition for which capsaicin nasal spray is the most effective treatment. However, the mechanisms underlying IR and the therapeutic action of capsaicin remain unknown. We sought to investigate the molecular and cellular bases of IR and the therapeutic action of capsaicin. Fourteen patients with IR and 12 healthy control subjects (HCs) were treated with intranasal capsaicin. The therapeutic effect was assessed in patients with IR by using visual analog scale and therapeutic response evaluation scores, and nasal hyperreactivity was evaluated by means of cold dry air provocation. Nasal samples served to measure the levels of neuromediators and expression of chemosensory cation channels, protein gene product 9.5 (PGP 9.5), and the mast cell marker c-kit. The effects of capsaicin were also tested in vitro on human nasal epithelial cells and mast cells. Patients with IR had higher baseline transient receptor potential cation channel subfamily V, receptor 1 (TRPV1) expression in the nasal mucosa and higher concentrations of substance P (SP) in nasal secretions than HCs. Symptomatic relief was observed in 11 of 14 patients with IR after capsaicin treatment. Expression of TRPV1; transient receptor potential cation channel subfamily M, receptor 8 (TRPM8); and PGP 9.5 was only reduced in patients with IR after capsaicin treatment. Capsaicin did not alter c-KIT expression or nasal epithelial morphology in patients with IR and HCs nor did it induce apoptosis or necrosis in cultured human nasal epithelial cells and mast cells. IR features an overexpression of TRPV1 in the nasal mucosa and increased SP levels in nasal secretions. Capsaicin exerts its therapeutic action by ablating the TRPV1-SP nociceptive signaling pathway in the nasal mucosa.